Performance Analysis Of Green Supply Chain Management Using AHP And OMAX Methods - Aditya Tri Pratama; Ernawati, Dira; Rahmawati, Nur (APIC, 2025)
The manufacturing industry in Indonesia has experienced significant growth, leading to a high level of urgency concerning environmental pollution. Currently, within the manufacturing sector, there is an increased emphasis on environmental protection and sustainable production, which has become a key priority for companies. One approach to preventing environmental pollution is the implementation of Green Supply Chain Management (GSCM). PT. XYZ is one of the companies that has not yet fully implemented this concept. This is evident from the considerable amount of waste and scrap materials from ship production that remain poorly managed. Based on these circumstances, this study was conducted with the objective of evaluating the performance level of Green Supply Chain Management at the company. The research adopts the Green SCOR model, using Analytical Hierarchy Process (AHP) for weighting and Objective Matrix (OMAX) for scoring. Data processing is carried out using five Green SCOR models: plan, source, make, deliver, and return, resulting in a total of 26 Key Performance Indicators (KPIs). Out of the 26 KPIs, 5 fall under the red category, 6 are categorized as yellow, and the remaining 15 are in the green category. The final performance score for Green SCM activities at the company is 7.890, which falls within the yellow category. This indicates an average performance level, where the achievement of the performance indicators has not yet reached the target, although it is nearing the desired goal.